PENGARUH PROFESIONALISME, INDEPENDENSI, KOMPETENSI, OBYEKTIFITAS DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT DI KANTOR AKUNTAN PUBLIK (KAP) SEMARANG - Alief Nafila Alfa P, 14.05.52.0113; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze empirically the influence of professionalism, competence, independence, objectivity and work experience on audit quality in the Semarang Public Accounting Firm (KAP). The population used in this study is all KAP auditors in Semarang City. The sampling method used is convinience sampling, which is the selection of samples based on convenience, so the author has the freedom to choose the fastest and easiest sample. In this study the dependent variable used is audit quality, while the independent variable consists of independence, auditor ethics, competence, auditor experience, and objectivity. Data analysis techniques using multiple linear regression analysis. The results showed that professionalism, competence, objectivity and work experience had a positive and not significant effect on audit quality. Independence has a significant positive effect on audit quality. Keywords: professionalism, independence, competence, objectivity and work experience.